2017
DOI: 10.4244/eij-d-15-00269
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and residual SYNTAX score in predicting outcomes after acute infarct angioplasty

Abstract: In STEMI patients undergoing PPCI, both bSS and rSS can predict mortality at 12 months. Every point on the rSS confers an additional 6% mortality risk. Calculation of the rSS after culprit lesion intervention may help guide management of non-culprit lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 0 publications
1
21
3
Order By: Relevance
“…As complete revascularization is not always achievable in acute setting, previous studies have examined the concept of reasonable incomplete revascularization in ACS, but not in CS. Previously, the cutoff has been most often set at rSS 8, or 12 points . In contrast to the earlier studies in non‐CS populations, we found no prognostic effect whether we used the rSS cutoff of 8 or 12 points.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…As complete revascularization is not always achievable in acute setting, previous studies have examined the concept of reasonable incomplete revascularization in ACS, but not in CS. Previously, the cutoff has been most often set at rSS 8, or 12 points . In contrast to the earlier studies in non‐CS populations, we found no prognostic effect whether we used the rSS cutoff of 8 or 12 points.…”
Section: Discussioncontrasting
confidence: 99%
“…The median bSS in this study was lower than in the original SYNTAX study, but higher than in previous studies concerning STEMI . The median bSS was higher than described in another CS population, yet the definition of CS in our study was stricter.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Farooq validated the prognostic impact of the rSS on adverse outcomes in the SYNTAX trial, which showed that the rSS is a powerful indicator of 5‐year mortality . The prognostic value of the rSS has also been confirmed for patients with multivessel CAD, unprotected left main disease, MI while undergoing primary PCI, complex disease treated with second‐generation drug‐eluting stents, and all PCI patients . However, no studies or subgroup analyses have been performed to determine whether the rSS is meaningful for patients with CRI.…”
Section: Discussionmentioning
confidence: 99%